Application of extremely non-equilibrium plasmas in the processing of nano and biomedical materials. (8th January 2015) - Mozetič, Miran; Primc, Gregor; Vesel, Alenka; Zaplotnik, Rok; Modic, Martina; Junkar, Ita; Recek, Nina; Klanjšek-Gunde, Marta; Guhy, Lukus; Sunkara, Mahendra K; Assensio, Maria C; Milošević, Slobodan; et al.
Abstract: Some applications of extremely non-equilibrium oxygen plasma for tailoring the surface properties of organic as well as inorganic materials are presented. Plasma of low or moderate ionization fraction and very high dissociation fraction is created by high frequency electrodeless discharges created in chambers made from a material of low recombination coefficient. The O atom density often exceeds 10 21 m −3 which allows for rapid functionalization of carbon-containing materials. Surface saturation with polar oxygen-rich groups is achieved in a fraction of a second and further exposure leads to etching. The etching is often non-uniform and results in nano-structuring of surface morphology. A combination of rich morphology and saturation with polar functional groups allows for a super-hydrophilic character of originally hydrophobic materials. Polymer composites are etched selectively so the polymer component is removed from the sample surface, leading to modified surface properties. Furthermore, such a treatment allows for distinguishing the distribution and orientation of fillers inside the polymer matrix. The exposure of inorganic materials to non-equilibrium oxygen plasma causes one-dimensional growth of metal oxide nanoparticles, thus representing a unique technique for the rapid catalyser-free growth of nanowires.